2010
DOI: 10.3109/02770900903518835
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Control of Severe Asthma

Abstract: Many patients with severe asthma have poor control of their disease. The number of exacerbations is the variable with the greatest effect on control of asthma. Knowledge of the disease and adherence to treatment are associated with better control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 24 publications
0
31
0
3
Order By: Relevance
“…Male mice have a high IFN-γ/IL-5 ratio and low allergen-specific IgE level, but they develop asthma despite this and may require treatment to help overcome these conditions. Furthermore, male children have higher theophylline clearance53 and lower drug adherence during asthma exacerbation,54 but controlling their asthma is relatively easier 55…”
Section: Sex Differences In the Effectiveness Of And Adverse Reactionmentioning
confidence: 99%
“…Male mice have a high IFN-γ/IL-5 ratio and low allergen-specific IgE level, but they develop asthma despite this and may require treatment to help overcome these conditions. Furthermore, male children have higher theophylline clearance53 and lower drug adherence during asthma exacerbation,54 but controlling their asthma is relatively easier 55…”
Section: Sex Differences In the Effectiveness Of And Adverse Reactionmentioning
confidence: 99%
“…The data extracted from each article included the elementary characteristics of the study (first author, year of publication, study population, sample size, follow-up duration, and follow-up loss), baseline characteristics of the participators (age at recruitment, gender, ethnicity, socioeconomic status, and smoking history), and clinical characteristics (diagnosis, duration, severity, lung function, asthma control status, asthma medications, adherence to treatment, and exacerbations during the previous year) (45,46). Study quality was assessed and scored independently by two reviewers (LZ and XZ) using the Newcastle-Ottawa Quality Assessment Scale (47).…”
Section: Details Of the Extracted Data And Quality Assessmentmentioning
confidence: 99%
“…Taken by itself, knowledge about asthma may not have a direct impact on the practical skills of disease management, but it contributes to patients' ability to adapt to the disease [1]. It has been shown that in patients with asthma, knowledge of the disease and adherence to treatment are associated with better control, better adherence and improved quality of life [2][3][4]. Thus, enhancing patients' asthma knowledge is an important preliminary step to achieving better outcomes in the longer term.…”
Section: Introductionmentioning
confidence: 99%